STUDENTS’ SPEAKING PERFORMANCE IN THE CONTEXT OF LANGUAGE LEARNING APTITUDE - Indra Sudrajat; Destiani, Ninda (JELA (Journal of English Language Teaching, Literature and Applied Linguistics), 2021)
The language learning aptitude research has become popular again lately after some redefining efforts to include creative and practical language-acquisition abilities. Therefore, this study is designed by involving students’ creativity and part of language acquisition (i. e. speaking performance). Recent works have shown that the discussion on aptitude is very much alive after a relatively silent period of about thirty years. Early studies have shown that the established language learning aptitude tests show high correlations with intelligence and controlled language production, but low correlations with free oral production and general communication skills. The conventional aptitude tests do not tell the whole story of a person’s second-language learning ability. To challenge the old findings, in this research, the students’ language learning aptitude which is measured by an aptitude test is correlated with their speaking performance. It is an extending work to be up-to-date with the present trend of English teaching- learning in classroom which plays an important role in second-language acquisition as well, i. e. free oral production and general communication skills. A well-established test format and instruments by expert involving some relevant elements has been adapted for the selected students and the feasibility of assessing speaking performance in an English course is evaluated empirically. The results showed that the test and the instrument provide a reliable and efficient method of assessing the students’ aptitude and speaking performance. Evidence of validity was obtained from various tasks, and from an analysis of the scores in terms of some aspects, which is known to be associated with different levels of aptitude and speaking performance.